2013
DOI: 10.1097/aap.0b013e31829f644b
|View full text |Cite
|
Sign up to set email alerts
|

Promising Effects of Intravenous Lipid Emulsion as an Antidote in Acute Tramadol Poisoning

Abstract: Intravenous lipid emulsion significantly reduced mortality due to acute toxicity with tramadol in rabbits, although increasing the ILE dose may cause reverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…A new study in a rabbit model has found that due to tramadol's lipophilic nature, treatment with intravenous lipid emulsion increased survival, reduced tramadol-induced tachycardia, normalised mean arterial and diastolic blood pressure, and prevented tramadol-related seizures. 54 Further studies are required to determine its use in clinical cases.…”
Section: Other Medications?mentioning
confidence: 99%
“…A new study in a rabbit model has found that due to tramadol's lipophilic nature, treatment with intravenous lipid emulsion increased survival, reduced tramadol-induced tachycardia, normalised mean arterial and diastolic blood pressure, and prevented tramadol-related seizures. 54 Further studies are required to determine its use in clinical cases.…”
Section: Other Medications?mentioning
confidence: 99%
“…In a study on 30 rabbis, ILE reduced tramadol-induced tachycardia when administered within 30 minutes of poisoning and showed positive effects on normalizing mean arterial pressure and diastolic blood pressure but it did not have major effect on systolic blood pressure. Intralipid also prevented tramadol-related seizures in low doses and reduced the frequency of increased CPK with higher doses [124].…”
Section: Treatmentmentioning
confidence: 89%
“…[ 13 , 105 , 106 , 107 ] Based on the lipid sequestration and redistribution mechanism, several preclinical studies and case reports have suggested the application of lipid emulsion to detoxify other hydrophilic anesthetic drugs such as propofol, cocaine and tramadol. [ 108 , 109 , 110 ]…”
Section: Pk Approaches: Nano‐antidotes Sequestering Anesthetics For D...mentioning
confidence: 99%
“…[13,[105][106][107] Based on the lipid sequestration and redistribution mechanism, several preclinical studies and case reports have suggested the application of lipid emulsion to detoxify other hydrophilic anesthetic drugs such as propofol, cocaine and tramadol. [108][109][110] However, there are still discrepancies regarding the effectiveness and widespread application of lipid rescue therapy. [111] Concerns about the lack of randomized and controlled clinical trials, heterogeneous efficacy, publication bias of underreported treatment failure, toxicity relapse of overdosed drugs and lipidrelated complications have hindered the official approval of lipid emulsion for any antidotal therapy.…”
Section: Lipid Emulsion Anionic Liposome/nanoparticle and Ph-gradient...mentioning
confidence: 99%